High speed sCMOS-based oblique plane microscopy applied to the study of calcium dynamics in cardiac myocytes - Sikkel,MB; Kumar,S; Maioli,V; Rowlands,C; Gordon,F; Harding,SE; Lyon,A; MacLeod,KT; Dunsby,CW (Journal of Biophotonics, 2016)
blique plane microscopy (OPM) is a form of light sheet microscopy that uses a single high numerical aperture microscope objective for both fluorescence excitation and collection. In this paper, measurements of the relative collection efficiency of OPM are presented. An OPM system incorporating two sCMOS cameras is then introduced that enables single isolated cardiac myocytes to be studied continuously for 22 seconds in two dimensions at 667 frames per second with 960 × 200 pixels and for 30 seconds with 960 × 200 × 20 voxels at 25 volumes per second. In both cases OPM is able to record in two spectral channels, enabling intracellular calcium to be studied via the probe Fluo-4 AM simultaneously with the sarcolemma and transverse tubule network via the membrane dye Cellmask Orange. The OPM system was then applied to determine the spatial origin of spontaneous calcium waves for the first time and to measure the cell transverse tubule structure at their point of origin. Further results are presented to demonstrate that the OPM system can also be used to study calcium spark parameters depending on their relationship to the transverse tubule structure.